Pemberdayaan Para Ibu Rumah Tangga di Kawasan Wisata Flamboyan Kota Palangka Raya Kalimantan Tengah sebagai Upaya Peningkatan Derajat Kesehatan dan Ekonomi Masyarakat - Nurul Qamariah; Rezqi Handayani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The Flamboyan residential area is one area that has great potential to be developed as a tourist attraction in the city of Palangkaraya so that it has business opportunities for the local community, especially housewives to increase family income. But the area also has health problems that must be immediately addressed to become a comfortable tourist area to visit. Community service activities carried out have the aim of improving the degree of health and economic status of the community in the Flamboyan tourist area through improving the skills and knowledge of housewives. The stages of this activity are counseling or socialization of prevention and treatment of infectious diseases as well as the socialization of clean and healthy living behavior, the practice of making Bawang Dayak Gummy, and the practice of processing haruan fish oil. Community service activities that have been carried out have received good appreciation from partners, this can be seen from the results of the evaluation conducted knowledge and skills that have been given can be practiced by partners directly and partners have felt the positive impact of the results of community service activities such as being able to do independent treatment for minor ailments that often affects family members.